Development of a prediction model to determine responders to conservative treatment in people with symptomatic hand osteoarthritis: A secondary analysis of a single-centre, randomised feasibility trial. (December 2022) - Magni, N.; Rice, D.; McNair, P.
Abstract: Background: Conservative treatments are beneficial for people with hand osteoarthritis (OA). Objective: It was the purpose of this study to develop and internally validate both a basic model and a more complex model that could predict responders to conservative treatments in people with hand OA. Design: This was a secondary analysis of a single-centre, randomised feasibility study. Methods: Fifty-nine participants (34 responders) with hand osteoarthritis were recruited from the general population. Participants were randomised to receive either advice alone, or advice in combination with blood flow restriction training (BFRT), or traditional high intensity training (HIT). Participants underwent supervised hand exercises three times per week for six weeks. The OMERACT-OARSI criteria were utilised to determine responders vs non responders to treatment at the end of six weeks. A basic logistic regression model (treatment type, expectations, adherence) and a more complex logistic regression model (basic model variables plus pain catastrophising and neuropathic pain features) were created. Discrimination ability, and calibration were assessed. Internal model validation through bootstrapping (200 repetitions) was utilised to calculate the prediction model optimism. Results: The results showed that the basic model presented with acceptable discrimination (optimism corrected c-statistic: 0.72, 95% CI 0.71–0.73) and calibration (slope = 1.41; intercept = 0.68). The more complex model had better discrimination but poorer calibration. Conclusion: A prediction tool was created to provide an individualised estimate of treatment response in people with hand OA. Future studies will need to validate this model in other groups of patients. Trial registration: https://www.anzctr.org.au/ - ACTRN12617001270303. Highlights: A basic prediction model for conservative treatment in hand OA was developed. Expectations, adherence, and type of treatment contribute to treatment outcomes. The model needs validation in another group of patients with hand OA.